Free Radical Scavenging Activities of Extracts from Mulberries - Qin, Wen; Zou, Biqun; Liu, Xianxian; Yi, Xianghui; Zhang, Ye (Asian Journal of Chemistry, 2012)
Under ultrasound, Mulberries were extracted with ethanol, acetone and water solvents to offer acetone extract (AE), ethanol extract (EE) and water extract (WE), respectively. Their free radical scavenging activities were evaluated against DPPH, ABTS+ and hydroxyl radicals, respectively. The results showed that all IC50 of acetone extract, ethanol extract and water extract were much lower than the standard value 10 mg/mL in these three assays, suggesting all these extracts displayed good radical scavenging activities. In addition, the extract solvents had important effect on their radical scavenging activities.